Islamic Communication on Environmental Issues: A Literature Review of Sustainability Messages in Da'wah - Fatimah Zahra (PT. Berkah Smart Academica, 2025)
This literature review examines the intersection of Islamic communication (Da'wah) and environmental sustainability, focusing on the messages conveyed within Da'wah to promote ecological awareness and action. The review synthesizes existing research to understand how Islamic principles are utilized to address environmental challenges. This study employs a qualitative approach, analyzing scholarly articles, books, and related publications to identify key themes, communication strategies, and the effectiveness of Da'wah in shaping environmental attitudes and behaviors. The findings reveal that Da'wah leverages Islamic teachings on stewardship, justice, and interconnectedness to foster a sense of responsibility toward the environment. Da'wah plays a crucial role in raising awareness, promoting sustainable practices, and fostering community engagement in environmental initiatives.